Efforts to Improve Learning Outcomes in the IPAS Subject for Grade IV Students Using Audio-Visual Media at SDN 01 Sido Mekar - Lestari Lestari; Dwilita Astuti; Bambang Ariyanto (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This research aims to improve learning outcomes in science using audio-visual media. As a natural science, it aims to educate students in understanding natural sciences, such as natural phenomena and how to understand scientific methods and then apply them with a scientific attitude. Science is also a field of study that studies the natural sciences, namely substances, both living and non-living things. Based on the results of the initial survey, with the majority of students being less active in participating in learning activities, student learning outcomes in science are still low, and many have not yet achieved the KKTP (Preparatory Competency Level). Based on these problems, the researcher made efforts to improve the learning process by using audio-visual media. This research is a Classroom Action Research (CAR) with data collection using several methods: observation, tests, and documents. Learning was conducted in two cycles, with 13 students from fourth grade participating in the study. Based on the data analysis, it can be concluded that: Student learning outcomes using audio-visual media are as follows: In the pre-cycle, 6 students (46.15%) achieved learning completion with an average score of 73.69. In the first cycle, 8 students (61.54%) achieved learning completion with an average score of 75.69. Furthermore, in the second cycle, student learning outcomes improved further, with 11 students (84.62%) achieved learning completion with an average score of 82.00, completing the learning. Therefore, it can be concluded that the use of audio-visual media can improve student learning outcomes in the fourth-grade science subject at SDN 01 Sidomekar. Keywords: Audio-visual media, Learning Outcomes, IPAS.